Impact of Hatha and Iyengar Yoga on Physical Function and Quality of Life in Knee Osteoarthritis: A Systematic Review - Bagus Gede Krisna Astayogi; Cokorda Krishna Dalem Pemayun; I Gusti Bagus Dharma Prakasa Musti; I Ketut Jayaningrat; Nyoman Gede Trisna Anandita; I Putu Adi Palguna; I Gusti Ayu Avitri Vardhayanti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Osteoarthritis (OA) is a chronic degenerative disorder that primarily affects the articular cartilage of synovial joints. This condition leads to pain, joint stiffness, decreased muscle performance, and decreased aerobic capacity, which can negatively impact a patient's quality of life (QOL) and increase their risk of disability. This systematic review aims to investigate the effectiveness of two non-pharmacological treatment regimens, Hatha yoga, and Iyengar yoga, on QOL, physical function, and mental health in patients with knee OA. Methods: This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. A comprehensive search was performed across three electronic databases: PubMed, Google Scholar, and ScienceDirect, to identify eligible studies that examined the beneficial effects of Hatha Yoga and Iyengar Yoga on improving physical function, mental health, and QOL in patients with knee OA. Results: Out of 61 reports initially identified, 51 were excluded based on the pre-defined inclusion and exclusion criteria. The results of this systematic review suggest that the combination of Hatha Yoga and Iyengar Yoga can enhance physical function, mental health, and QOL in patients with knee OA. Conclusion: Both Hatha Yoga and Iyengar Yoga can serve as effective complementary treatments alongside conventional treatment to improve the overall well-being of individuals with knee OA.